La garantía del juicio por jurados en la etapa recursiva - Varela, Natalia (2017)
Citizen participation in criminal trials has been foreseen three times in our National Constitution since 1994. However, trials by juries began to take place in our country only in 2006, today there are still few provinces that have adopted its codes of criminal procedure to the constitutional precept. Assuming the position of jurists who consider the trial by jury a guarantee, this work will try to highlight the tension that is generated with the guarantee of effective remedy, product of the lack of harmonization of legislation.